2018
DOI: 10.1097/tp.0000000000002173
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Hepatitis B Surface Antibody in Addition to Hepatitis B Core Antibody Confers Protection Against Hepatitis B Virus Infection in Hepatitis B Surface Antigen–negative Patients Undergoing Kidney Transplantation

Abstract: The presence of anti-HBs confers protection against HBV infection. We recommend monitoring for HBV infection after KT in HBsAg(-) anti-HBc(+) anti-HBs(-) patients, but not in HBsAg(-) anti-HBc(+) anti-HBs(+) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The risk of HBsAg reversion is low in recipients who are HBsAg negative and anti-HBc positive. In a Korean cohort study of 951 recipients of kidney transplantation recipients with seronegative HBsAg/seropositive anti-HBc, the HBsAg reversion rate was 5.6% for anti-HBs negative patients, but there was no difference between anti-HBs-positive and anti-HBc-negative recipients [516]. However, because HBsAg reversion followed by liver failure was reported in recipients with seronegative HBsAg/seropositive anti-HBc, hepatitis B reactivation should be monitored regularly.…”
Section: Management In Special Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of HBsAg reversion is low in recipients who are HBsAg negative and anti-HBc positive. In a Korean cohort study of 951 recipients of kidney transplantation recipients with seronegative HBsAg/seropositive anti-HBc, the HBsAg reversion rate was 5.6% for anti-HBs negative patients, but there was no difference between anti-HBs-positive and anti-HBc-negative recipients [516]. However, because HBsAg reversion followed by liver failure was reported in recipients with seronegative HBsAg/seropositive anti-HBc, hepatitis B reactivation should be monitored regularly.…”
Section: Management In Special Conditionsmentioning
confidence: 99%
“…In patients who are ABO-incompatible and highly sensitized, rituximab is commonly used prior to renal transplantation. However, it can lead to liver failure in those with past HBV infection due to HBsAg reversion or HBV DNA redetection, albeit this risk is very low at low rituximab doses (200 mg) [516-518].…”
Section: Management In Special Conditionsmentioning
confidence: 99%
“…[ 17 ] More recently, a retrospective study in Korea reported that the post-transplantation HBV infection rate was higher in anti-HBc-positive patients and undetectable anti-HBs than in those with detectable anti-HBs (5.6% vs 1.2%, P < .001). [ 22 ] In our study, anti-HBs titers prior to transplantation were available in 2 of the 3 cases of HBV reactivation, and in both patients they were <10 mIU/mL.…”
Section: Discussionmentioning
confidence: 91%
“…Cho et al [27] similarly observed no HBV reactivation in patients with prechemotherapy HBsAb titers >100 IU/mL, but the incidence of HBV reactivation was 8.3% at 6 months and 17.3% at 24 months postchemotherapy in those with HBsAb titers below this threshold. In addition, Jae Wan Jeon et al [28] found a significant difference in HBV infection rates between HBcAb(+) HBsAb(+) patients and HBcAb(+)HBsAb(-) patients (1.2% versus 5.6%; P < .001) in 1959 patients who underwent renal transplantation. Our results confirmed the protective function of HBsAbs in HBsAg(-)/HBcAb(+) HSCT recipients.…”
Section: Discussionmentioning
confidence: 98%